VALIDATION OF ANALYTICAL METHOD OF 2,5-HEXANEDIONE ON URINE BY GAS CHROMATOGRAPHY - MUCHTARIDI, MUCHTARIDI; Megawati, Kurnia; Saputri, Febrina Amelia; M., Mulyana (International Journal of Applied Pharmaceutics, 2019)
Objective: The purpose of this study was to obtain a valid analytical method for determining the level of 2,5-hexanedione in the urine of oil industry workers. Methods: Gas Chromatography (GC) was employed to analyze 2,5-hexanedione in the urine. The analysis was done using HP-5 (Crosslinked methyl siloxane) capillary columns 30 m x 0.320 mm long, film thickness 0.25 μm. The temperature of the detector temperature was 300 °C, and the injector temperature was 250 °C. The helium gas flow rate was 2 ml/min. The detector was Flame Ionization Detection (FID). Parameters of system suitability test and validation were obtained. Results: This study results that the method of analysis 2,5-hexanedione in urine by Gas Chromatography (GC) confirm the requirements of the validation method with a linearity was 0.99963, accuracy was in the range of 99.16% to 114.13%, the precision with % coefficient of variation was 1.65% to 5.16%, % coefficient variation of specificity was 0.027%, limit of detection was 0.054 μg/ml and limit of quantification was 0.18 μg/ml. Conclusion: The proposed GC method meets the acceptance criteria of validation parameters and can be applied for routine analysis.